2008
DOI: 10.1074/jbc.m708735200
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick Type C1 I1061T Mutant Encodes a Functional Protein That Is Selected for Endoplasmic Reticulum-associated Degradation Due to Protein Misfolding

Abstract: Over 200 disease-causing mutations have been identified in the NPC1 gene. The most prevalent mutation, NPC1 I1061T , is predicted to lie within the cysteine-rich luminal domain and is associated with the classic juvenile-onset phenotype of Niemann-Pick type C disease. To gain insight into the molecular mechanism by which the NPC1 I1061T mutation causes disease, we examined expression of the mutant protein in human fibroblasts homozygous for the NPC1 I1061T mutation. Despite similar NPC1 mRNA levels between wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
227
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(257 citation statements)
references
References 41 publications
29
227
0
1
Order By: Relevance
“…Our data suggest that these mutations may render the NPC1 protein unstable and rapidly degraded but they would not completely abolish the NPC1 functionality. These finding are in line with those described by Gelsthorpe et al (Gelsthorpe et al 2008) showing that a twofold overexpression of GFP-tagged NPC1 I1061T in transient transfected npc1-deficient CHO cells was enough to partially restore the cholesterol trafficking. These authors postulated that a percentage of 2-5% of the nascent NPC1 I1061T mutant protein would be able to fold properly, escape the ER quality control and reach the lysosome/LE compartment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data suggest that these mutations may render the NPC1 protein unstable and rapidly degraded but they would not completely abolish the NPC1 functionality. These finding are in line with those described by Gelsthorpe et al (Gelsthorpe et al 2008) showing that a twofold overexpression of GFP-tagged NPC1 I1061T in transient transfected npc1-deficient CHO cells was enough to partially restore the cholesterol trafficking. These authors postulated that a percentage of 2-5% of the nascent NPC1 I1061T mutant protein would be able to fold properly, escape the ER quality control and reach the lysosome/LE compartment.…”
Section: Discussionsupporting
confidence: 92%
“…Transient transfection of npc1-deficient CHO cells with GFP-tagged NPC1-I1061T led to lysosomal localization of the mutant protein and functional complementation of the NPC mutant phenotype. Therefore, it has been suggested that therapeutic strategies directed to enhance the amount of mutated protein, such as the use of chemical chaperones, may rescue the pathologic phenotype in patients carrying the p.I1061T mutation (Gelsthorpe et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3A). It is essential to establish the localization of the mutants, as many NPC1 mutations lead to misfolding and ER-associated degradation (25,26). Although correctly localized, NPC1ΔΩ-A blocks cholesterol transport out of late endosomes, as does the NPC1-P691S mutant; NPC1ΔΨ loses 50% activity compared with NPC1-WT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ref. 21). Thus, before concluding that the R518Q mutation was a function-blocking mutation, it was important to verify that the NPC1 R518Q protein is capable of transport to lysosomes.…”
Section: Figurementioning
confidence: 99%